Behaviors related to Quilombola women's health: a social representations study - Ingrid Fabiane Santos da Silva; Ivaneide Leal Ataíde Rodrigues; Laura Maria Vidal Nogueira; Iaci Proença Palmeira; Márcia de Assunção Ferreira
ABSTRACT Objective: To Identify Quilombola women's social representations about health care and to characterize practices performed by them. Method: a descriptive, qualitative study, applying the Social Representations Theory, conducted with 30 women from a Quilombola community in the Brazilian Amazon. Individual interviews and thematic content analysis were carried out. Results: Health care practices are related to the home, people, families, and environment, indicating a Quilombola women's extended understanding about health care. In the first instance, natural resources derived from traditional knowledge and use of herbs are applied, in the second instance, the official health system, with the mother-woman being the main caregiver of the family. Final Considerations: the mother enables a health care in the family daily life, and she is the main way of access health professionals have to enter the Quilombola community and provide proper care from the official health system to the group.